Nutrition and health of edible insects. Issue 3 (May 2020) - van Huis, Arnold
Abstract : Purpose of review: Elucidate the effect of insects as feed and food on nutrition and health of humans and animals. Recent findings: A new sector is developing of insects as food and feed. The academic interest is growing exponentially. In addition to their high nutritional values, there are also health benefits. These relate to prebiotic effects of insect products, such as chitin on humans and animals. Insects have a large reservoir of antimicrobial peptides. Some insect species have shown to have antioxidant properties. Summary: The increasing demand for meat and the limited amount of land availability prompt the search for alternative protein sources. Insects require less land and have a lower environmental impact than meat products. In addition to having a high nutritional value, they have also health benefits. Several edible insect species can be grown on organic side streams, in this way contributing to a circular economy. The number of scientific articles increased exponentially, and more than 290 start-ups are now engaging in its production and marketing. Food safety issues are not a major issue but need to be carefully checked when organic waste streams are used. The main strategies related to consumer issues are disguising the insects in familiar products and making them tasty.